Answer:
Step-by-step explanation:
Answer:
The factors of given polynomial x =-1 , -2 and x =3
Step-by-step explanation:
<u><em>Step(i):</em></u>-
Given the polynomial
f(x) = x³ - 7x -6
put x =-1
f(-1) = (-1 )³- 7(-1) - 6 = -1+7-6=0
(x+1) is a one factor
By using synthetic division
x³ x² x constant
x=-1 ↓ 1 0 -7 -6
<u>↓ 0 -1 1 6</u>
<u> 1 -1 -6 0 </u>
<u />
<em>The polynomial x² - x - 6 </em>
<u><em>Step(ii):-</em></u>
The factors ( x+1)(x² - x - 6 ) = 0
x = -1 and x² - x - 6 =0
x =-1 and x² - 3x + 2 x - 6 =0
x =-1 and x (x -3) + 2( x-3) =0
x =-1 and (x+2)(x-3) =0
<u><em>Final answer:-</em></u>
The factors of given polynomial x =-1 , -2 and x =3
Answer:
11n
Step-by-step explanation:
We don't know the value of N, so we leave that the same.
3 to the second power, (3x3)= 9.
We have to add 2 to 9, so 9+2=11
Add your n to the end, and your answer is 11n.
48.
For the rectangle, 4x6 =24
For the triangle, area of the triangle is 1/2 x base x height. So, 24.
Add together is 48